Having a bad month: general versus specific effects of stress on crime - Felson, Richard B. (Journal of quantitative criminology, 2012)
We examine whether particular types of stress are related to particular types of crime or whether all types of stress are related to all types of crime. Our estimates are based on analyses of within-individual change over a 36 month period among recently incarcerated offenders. We find that assault is most strongly related to family stress, suggesting that conflicts between family members lead to assault. Economic crimes (property crimes and selling illicit drugs) are most clearly related to financial stress, suggesting that these crimes often reflect attempts to resolve financial problems. On the other hand, crime is generally unrelated to stress from illness/injury, death, and work. The results support the idea that criminal behavior is a focused response to specific types of problems rather than a general response to stress. They are more consistent with explanations that focus on perceived rewards and costs (e.g., the rational-choice approach) than with explanations that portray negative affect as a generalized impetus toward violence or crime (e.g., frustration aggression approaches).